HUBUNGAN TINGKAT PENGETAHUAN TERHADAP MINAT IBU UNTUK MENGIKUTI PROGRAM KB DI DESA BAHUNG SIBATU-BATU KECAMATAN SEI DADAP KABUPATEN ASAHAN TAHUN 2019 - NURAINI SURYATI POHAN (LP2MTBM MAKARIOZ, 2021)
This study aims to find out the relationship between the level of knowledge and the interest of mothers to join the kbprogram. This research method uses descriptive design correlation with Cross Sectional approach. The research wasconducted in Bahung Sibatu-batu Village, Sei Dadap District, Asahan Regency, against 32 mothers who were taken usingPurposive Sampling technique by considering the inclusion criteria. The measuring instrument used was a questionnaire with34 statements developed by researchers. The analysis used is univariate and bivariate analysis with Chi-square test. Theresults showed that there is a relationship between the level of knowledge and the interest of the mother to participate in ameaningful kb program (P-Value = 0.000; a = 0.05). Based on the results of this research, it is expected to local healthagencies to further improve counseling on kb programs that aim to increase maternal knowledge about kb programs that caninfluence the interest of mothers to join the kb program in Bahung Sibatu-batu Village.